1997
DOI: 10.1210/jcem.82.11.4349
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic Role of Prolactin Supplementation in Ovarian Stimulation forin VitroFertilization: The Bromocriptine-Rebound Method

Abstract: In a prospective randomized study, we examined whether a novel method of ovarian stimulation, the bromocriptine-rebound method, improves in vitro fertilization (IVF) outcomes compared with the conventional long protocol using GnRH agonist and human menopausal gonadotropin (hMG). Ovulatory women with previous failed IVF-embryo transfer using the long protocol were prospectively assigned to either the bromocriptine-rebound method (group 1, 82 cycles) or the long protocol (group 2, 80 cycles). The bromocriptine-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Human prolactin (hPRL), a protein hormone primarily secreted by the anterior pituitary, has a remarkably wide spectrum of biological activities [1]. Whereas PRL is best known for its stimulation of lactation, and growth and development of the mammary gland [2], it has also been shown to mediate a variety of physiological processes, including growth and maturation of oocytes [3], immune modulation [4] and osmoregulation [5]. Basically a single‐chain protein with a molecular mass of 23000 Da and three intramolecular disulphide bridges, PRL shows significant molecular polymorphism, including a varying percentage of the glycosylated form, which could underlie its diverse properties [1].…”
Section: Introductionmentioning
confidence: 99%
“…Human prolactin (hPRL), a protein hormone primarily secreted by the anterior pituitary, has a remarkably wide spectrum of biological activities [1]. Whereas PRL is best known for its stimulation of lactation, and growth and development of the mammary gland [2], it has also been shown to mediate a variety of physiological processes, including growth and maturation of oocytes [3], immune modulation [4] and osmoregulation [5]. Basically a single‐chain protein with a molecular mass of 23000 Da and three intramolecular disulphide bridges, PRL shows significant molecular polymorphism, including a varying percentage of the glycosylated form, which could underlie its diverse properties [1].…”
Section: Introductionmentioning
confidence: 99%
“…The role of prolactin in restoring the responsiveness of granulosa cells to stimulation was explored in an older study. Thus, Jinno et al [ 87 ] proposed a new method of ovarian stimulation for IVF in patients with previous IVF failure, the bromocriptine rebound (BR) method [ 87 ]. They administrated bromocriptine from day 4 of the preceding cycle until 7 days before stimulation in patients treated with long agonist protocol and HMG.…”
Section: The Role Of Dopamine Agonist Administration In Ivf Treatmentmentioning
confidence: 99%
“…They administrated bromocriptine from day 4 of the preceding cycle until 7 days before stimulation in patients treated with long agonist protocol and HMG. They reported that patients treated with the BR method had higher numbers of follicles, fertilized oocytes, embryos with superior morphology, clinical pregnancy and live birth rates in comparison with patients who did not receive bromocriptine ( Table 1 ) [ 87 ]. Prolactin levels were also significantly higher in patients treated with bromocriptine and were correlated with the number of superior embryos [ 87 ].…”
Section: The Role Of Dopamine Agonist Administration In Ivf Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…К настоящему времени установлено, что гормон гипофиза пролактин (ПРЛ) влияет на овариальную функцию самок и может позитивно модулировать созревание ооцитов и их способность к эмбриональному развитию (17)(18)(19)(20). Рецепторы этого гормона или его мРНК выявлены в ооцитах и сопряженных с ними клетках кумулюса у различных видов млекопитающих, включая коров (20)(21)(22)(23).…”
unclassified